Drivers and Barriers to Teacher-Led Change in Botswana’s Schools: A Qualitative Study - Moremi, Mbiganyi; Mafuraga, Mbizo; Mogotsi, Benjamin (International Journal of Language and Literary Studies, 2026)
Schools often grapple with factors that drive or restrain change. Managing change is necessary for schools to fulfil their mandates. In Botswana schools, change factors resulted in the way teachers think and act in managing education programmes. Mindset change is one of the factors that drive or impedes teachers from embracing change effectively in their schools. Hence, this study explored how teacher led changes could drive or impede the necessary change in schools. Qualitative research method was adopted in this study and data was collected from 48 teachers in selected schools in Botswana. The findings revealed that lack of change management structures in schools was a major drawback in the implementation of change initiatives. Such structures would make teachers be up to date with current trends in education. The findings further highlighted how the Force Field Analysis (FFA), a framework or management technique that deals with forces for or against change could be applied in schools. The study recommends the introduction of Change Agents in schools, who would be instrumental in bringing and monitoring the impact of change affecting teachers and students.